A new titinopathy: Childhood-juvenile onset Emery-Dreifuss–like phenotype without cardiomyopathy. (15th December 2015) - De Cid, Rafael; Ben Yaou, Rabah; Roudaut, Carinne; Charton, Karine; Baulande, Sylvain; Leturcq, France; Romero, Norma Beatriz; Malfatti, Edoardo; Beuvin, Maud; Vihola, Anna; Criqui, Audrey; Nelson, Isabelle; et al.
Abstract : Objective: To identify the genetic defects present in 3 families with muscular dystrophy, contractures, and calpain 3 deficiency. Methods: We performed targeted exome sequencing on one patient presenting a deficiency in calpain 3 on Western blot but for which mutations in the gene had been excluded. The identification of a homozygous truncating mutation in the M-line part of titin prompted us to sequence this region in 2 additional patients presenting similar clinical and biochemical characteristics. Results: The 3 patients shared similar features: coexistence of limb-girdle weakness and early-onset diffuse joint contractures without cardiomyopathy. The biopsies showed rimmed vacuoles, a dystrophic pattern, and secondary reduction in calpain 3. We identified a novel homozygous mutation in the exon Mex3 of the TTN gene in the first patient. At protein level, this mutation introduces a stop codon at the level of Mex3. Interestingly, we identified truncating mutations in both alleles in the same region of the TTN gene in patients from 2 additional families. Molecular protein analyses confirm loss of the C-ter part of titin. Conclusions: Our study broadens the phenotype of titinopathies with the report of a new clinical entity with prominent contractures and no cardiac abnormality and where the recessive mutations lead to truncation of the M-line titin and secondary calpain 3 deficiency.